Deixis in the novel Murder on the orient express - Atika Pertiwi; Cita Hikmah Yanti (Language and Education Journal, 2020)
This study which entitled “Deixis in The Novel Murder on the Orient Express by Agatha Christie” Deixis described the relationship between language and context and the objectives of this study were (1) to find out the utterances of a major character, M. Poirot, and types of the deixis in The Novel Murder on the Orient Express by Agatha Christie. (2) to describe the reference of each type of deixis in the Novel Murder on the Orient Express. This study applied the descriptive qualitative method. The result of this study showed that there were three types of deixis found in the utterances of a major character, M. Poirot in the novel Murder on the Orient Express, namely personal deixis (73 data), temporal deixis (18 data), and spatial deixis (9 data). The referent of the personal deixis found referred to all passenger in the Orient Express, temporal deixis refers to the time of utterance was uttered and the murder of Ratchett occurred, spatial deixis referred to the Orient Express itself.